Eksplorasi Sastra Lisan â€œBiseang Labboroâ€ Berbasis Kearifan Lokal untuk Pengembangan Ekowisata: Studi Kasus Desa Wisata Alam di Maros - Kasma F. Amin; Martini Martini (GHANCARAN: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2025)
This study aims to explore the oral literature "Biseang Labboro" in supporting the potential of natural tourism in Maros Regency. The methods used are recording, interviews, and literature review to collect data related to oral literature and ecotourism potential. The ecostrast approach is used to see the relationship between living things and their environment which is reflected in literary works; includes exploring how people appreciate nature by connecting natural events that have occurred; nature is expressed in oral literature, and how oral literature can be developed for the advancement of ecotourism. The analysis technique uses the AGIL theory approach of Talcott Parsons (AGIL). The findings show that the Biseang Labboro oral story artifacts have similarities with shipwrecks. These artifacts support the story as a form of environmental adaptation. The purpose of storytelling is to teach the values of local wisdom, environmental issues, and nature conservation. The oral story contains an integration of Bugis Makassar culture and Chinese culture. Pilgrims from the Chinese community who perform rituals of respect for their ancestors as a form of latency of oral literature, and the Maros Regency government has recorded and protected cultural assets such as traditional music workshops accompanying oral literature.